The relationship between defense, education and health expenditures in selected Asian countries - Mohd Tahir, Hirnissa; Habibullah, Muzafar Shah; Abdul Hamid, Baharom (Canadian Center of Science and Education, 2009)
This study explores the inter-relationship between military expenditure, education expenditure and health expenditure in eight selected Asian countries namely Malaysia, Indonesia, Singapore, Philippines, Bangladesh, Nepal, Sri Lanka and South Korea. Autoregressive Distributed Lag-Restricted Error Correction Model (ARDL-RECM) procedure was utilized in the analysis. The empirical results suggest that, except for the case of Malaysia and Sri Lanka, whereby no meaningful interrelationship was detected between these three variables, the results for the rest of the countries are mixed, with differing granger causality being detected among these variables. The mixed results obtained in this study is an indicator of differing policy being implemented and will result in varying implication. Generally the error correction term is significant. Implying there is long-run relationship between defense spending, education and health expenditure.